Governing the Galleys: Jurisdiction, Justice, and Trade in the Squadrons of the Hispanic Monarchy (Sixteenth-Seventeenth Centuries) - Lomas Consuelo López-Morillas, Manuel (Mediterranean Reconfigurations, 2019)
In Governing the Galleys, Manuel Lomas analyses the political, legal and economic impact of the development of the Spanish Navy in the Early Modern Mediterranean (sixteenth - seventeenth centuries). Readership: All interested in the maritime history of Spain, the history of the galleys, the history of warfare, jurisdictional systems, and the history of the early modern Mediterranean.